HISTOPATHOLOGICAL ARRAY OF HEAD AND NECK LESIONS: IN A TERTIARY CARE CENTRE - Dr. Ankitha Patil,Dr. Ramesh B.H, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Head and neck lesions encompass a wide spectrum of pathologies ranging from benign and inflammatoryconditions to malignant neoplasms. Due to their complex anatomy and diverse tissue origin, lesions in thisregion often pose diagnostic challenges. Histopathological examination remains the gold standard for definitive diagnosis, guiding treatment and prognosis.